Potret Kehidupan Ekonomi pada Masa Nabi (Aplikasi Mudharabah dalam Perbankan Syariah) - Muhammad Iqbal (Department of Islamic Banking, Faculty of Islamic Economics and Business, UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
This research aims to provide a complete picture of the economic portrait at the time of the prophet, the status of the Mudharabah hadith and how the application of Mudarabah in Islamic banking is. Muhammad started the construction of Medina without definite financial sources, while the distribution of wealth was also unequal. The emigrants had no wealth because they had left their wealth in Mecca. Muhammad brought brotherhood between the Muhajirin and the Ansar so that by itself there was a redistribution of wealth, this policy was very important as an initial strategy for the development of Medina. Furthermore, to rotate the economy, encourage business cooperation among community members such as muzaraah, mudarabah, and musaqah so that there is an increase in productivity. At first, Mudarabah was considered as the backbone of Islamic banking operations. In practice, this type of profit-sharing financing is only a small part of the financing provided by Islamic banks around the world.